ANALYSIS OF STUDENT'S VOCABULARY DIFFICULTY IN NARRATIVE TEXTS - Achmad Fanani; Mohammad Bakhtiar Arifianto; Afifa S. Zulfikar; Aizun Najih (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2022)
This research aims to analyze learners' vocabulary mastery skills in narrative text. For example, in what kind of word class do the learner have difficulties, how it manifests, and how do the difficulties occur. This research uses only three-word classes: Verb, Noun, and Adjective. To analyze the data, the researcher used the descriptive qualitative method. The participants of this study consist of 4 students at tenth graders of MA Umar Zahid Perak with a score below minimum competency in the final semester test. The data were collected by giving respondents a test on narrative text. This research gives information about students' vocabulary mastery in narrative text. There are four problems encountered by students, namely: Incorrect active/passive voice, diction selection errors, incorrect word order, and incorrect word class. Most errors occur in the Verb word class, and the most frequent error is incorrect active/passive voice. Based on the results of this study, the teacher should anticipate identified errors in the categories of the verb, noun, and adjective.